2022
DOI: 10.1159/000526170
|View full text |Cite
|
Sign up to set email alerts
|

Fifteen Years after Sleeve Gastrectomy: Gastroscopies, Manometries, and 24-h pH-Metries in a Long-Term Follow-Up: A Multicenter Study

Abstract: Introduction: Sleeve gastrectomy (SG) is the most common bariatric operation with over 340,000 procedures per year. There are only few studies presenting follow-up results >10 years in the literature today. The aim of this study was the objective evaluation of long-term outcomes of at least 15 years after SG in non-converted patients. Methods: This study (multicenter cross-sectional; university-hospital based) includes all non-converted patients with primary SG before December 2005 at participating bariatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…These results have also been reported in rats at 5 weeks [20], 12 weeks [21], and 16 weeks after SG [21]. In humans, weight regain after SG is also often observed after 2 or 3 postoperative years, and it is always observed in studies with 10-or 15-years postoperative follow-up [14][15][16][17].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…These results have also been reported in rats at 5 weeks [20], 12 weeks [21], and 16 weeks after SG [21]. In humans, weight regain after SG is also often observed after 2 or 3 postoperative years, and it is always observed in studies with 10-or 15-years postoperative follow-up [14][15][16][17].…”
Section: Discussionsupporting
confidence: 69%
“…To our knowledge, only one study has reported the results of gastric biopsies performed at 15 years postoperatively in 16 patients. The authors found "active gastritis" in 75% of the 16 patients, but no other type of gastric lesion was described [17]. Furthermore, the prevalence of gastric intestinal metaplasia in postoperative gastric biopsies has never been reported in humans, whereas this prevalence is estimated to be approximately 2.7% in gastric specimens and gastric biopsies performed during preoperative endoscopy, according to a recent review by Wang et al [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparing the results of this study to the literature available on SG [ 27 ], one can summarize that acid reflux is a problem in the long-term follow-up after SG but seems to improve after OAGB. Nevertheless, the increasing rates of non-acid reflux after OAGB are a potentially dangerous finding that must be kept in mind.…”
Section: Discussionsupporting
confidence: 51%